Assessment of the commitment to vaccination of outpatient doctors - Snezhana D. Timoshkova; Marina V. Fedoseenko; Dina S. Rusinova; Galina P. Glazkova; Leyla S. Namazova-Baranova (Union of pediatricians of Russia, 2024)
Background. The commitment to vaccination of outpatient doctors is one of the factors that affects patients' confidence in preventive vaccinations and, as a result, the incidence of controlled infections. Unfortunately, emotionally colored information is currently spreading among the population faster than scientifically proven facts all over the world.The aim of this study is the examine of the level of knowledge and attitude to vaccination of doctors in one of the children's polyclinics in Moscow.Methods. An anonymous questionnaire survey was conducted among medical doctors of different specialties who expressed their attitude to various aspects of immunoprophylaxis and demonstrated knowledge in this field. Results. The survey demonstrated a positive attitude of respondents towards immunization, while some of them showed a cautious attitude towards the effectiveness and safety of vaccines, misconceptions (erroneous assumptions), increased susceptibility to "myths" about preventive vaccinations.Conclusion. The level of knowledge of medical doctors on vaccine prevention within a single health care institution range from insufficient training, including misconceptions, to a high level of knowledge and commitment regarding immunization. It is necessary to regularly maintain current theoretical knowledge of doctors and consolidate it in practice.